Mixed language processing increases cross-language phonetic transfer in Bengali–English bilinguals - Mitra, Auromita; Dutta, Indranil (Bilingualism (Cambridge, England), 2023)
This study investigates the phonetic outcome of mixed-language speech in Bengali and Indian English, towards understanding cross-language interaction in highly proficient bilinguals. We compare spectral properties of L2 vowels [æ] (common to L1, L2) and [ʌ] (absent in L1) in code-switched (mixed) vs. nonswitched productions. Results reveal asymmetrical shifts in both vowels during mixed productions, towards related L1 categories. We interpret this as a temporary increase in cross-language phonetic interaction during mixed-language use, leading to a shift towards L1 norms, evidencing transfer effects on L2 vowels. We elicit mixed productions through two tasks: cued picture-naming and code-switching, to assess if experimental paradigm independently influences the behavior under study. Results reveal parallel patterns, but small magnitude differences, across paradigms. We discuss these findings in light of recent proposals about asymmetries in short-term phonetic interaction, postulated discursive factors in code-switching, and the issue of comparability between paradigms in transfer studies.